Varying Number of Selfish Nodes based Simulation of AODV Routing Protocol in MANET using Reputation Based Scheme. (International Journal of Engineering and Computer Science, 2018)
Unlike in fixed networks the Mobile Ad Hoc networks needs more security mechanisms. Attackers may intrude into the network through the subverted nodes. The network topology is highly dynamic as nodes frequently join or leave the network, and roam in the network. In spite of its dynamic nature, mobile users request security services as they move from one place to another. The security solution should protect each node in the network and the security of the entire networks relies on the collective protection of all the nodes. The security solution should protect the network from both the inside and outside intruders into the system. In this paper we implemented AODV protocol based on reputation scheme to detect the selfish  node  and  the  evaluation  will be done  through  performance  metrics  (Packet  delivery  ratio,  Average  end to end delay, Average Throughput) in Network Simulator